MANAJEMEN LEAN PADA LAYANAN KEMOTERAPI ANAK RAWAT INAP DI RUMAH SAKIT CIPTO MANGUNKUSUMO - Teny Tjitra Sari; Andreasta Meliala; Firman (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2022)
Background: Cancer in children has high morbidity and mortality.Retinoblastoma is the most common solid tumor in children at theCipta Mangunkusumo Hospital (RSCM). Chemotherapy is one ofthe therapeutic modalities, interdisciplinary and many procedures.Lean management continuously reduces waste and improves work flow.Objective: This study used lean management to determine theefficiency of health care in teaching hospital.Methods: Action research was conducted at RSCM. Sampling by purposive sampling that represents the role in the flow of the service process. The observation guide uses cycle time observationsheets, value-added analysis sheets, waiting time and lead time.The waste found is listed in the DOWNTIME matrix. Observationswere made on inpatient chemotherapy services for children andthen a diagnosis was made using Value Stream Mapping. TheKaizen team consisted of pharmacists, nurses, doctors doing a plan-do-study-action, prepared an intervention plan, and conductedpost-intervention observations. The 5S method is used to improveservice flow.Results: In this study, patients with retinoblastoma in class III inpatient ward included were 7 patients in the pre-intervention group and 16 patients in the postintervention group. Major decreases in lead time happened in the subprocesses of ordering chemotherapy (75%), decision-making of chemotherapy administration (55%) andfilling of the resume (41%). Lead time process in chemotherapy administration for retinoblastoma changed from 48 hours, 36 minutes(more than 2 days) to 38 hours, 38 minutes (1.6 days or less than2 days). The efficiency of the process was measured using valueadded ratio which showed changes from 33% to 37%.Conclusion: Lean management applied in the process of chemotherapy administration in the inpatient wards increased theefficiency of the process.